Ответы и объяснения

  • Участник Знаний
2013-03-11T10:39:37+04:00

 Решите уравнение - решение  во вложении

Лучший Ответ!
  • Участник Знаний
2013-03-11T10:40:57+04:00

2√(2x-8) - √(9-6x+х^2) + 1=0

2√2*√(x-4)= √(9-6x+х^2)- 1

2√2*√(x-4)= √(x-3)^2- 1    -сокращаем квадрат под корнем

2√2*√(x-4)= (x-3)- 1=x-4

2√2 = √(x-4)     -обе части возведем в квадрат

(2√2)^2 =  | x-4 |

| x-4 | = 8

x -4 = 8  ;  x=12

Или

- x – 4 = 8 ; x=4

 

Проверка корней

2√(2*4-8) - √(9-6*4+4^2) + 1= 0 – 1 +1 =0

2√(2*12-8) - √(9-6*12+12^2) + 1= 8  -9 +1 =0

ОТВЕТ     4  ;  12